Guidelines for food systems dialogues at sub-national levels in Vietnam - Hanh Tho, Pham Thi; Huynh Thi, Tuyen Thanh; Nguyen, Quoc Minh (2025)
The guidelines support provincial actors in designing and facilitating food systems dialogues as part of the sub-national food systems process to co-develop their Provincial Implementation Plan (PIP), hereby contributing to the advancement of the National Action Plan on Food Systems Transformation towards Responsibility, Transparency, and Sustainability (NAP-FST). The guidelines for sub-national food systems dialogues draw on the experiences of the Dialogue Co-Convenors and the partners in organizing the national and regional Food Systems Summit Dialogues in Vietnam in 2021. They have been adapted, refined, and piloted at sub-national levels in Dong Thap and Son La provinces between August and December 2024.